Islamic Legal Review of Pre-Eid Money Exchange Practices and Exchange Rate Impacts in Medan - Zahara, Fatimah (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to analyze the practice of exchanging Rupiah money ahead of Lebaran in Medan City and its impact from the perspective of Islamic law and economics. The phenomenon of non-official money changers that is rampant in various locations such as Medan Tembung, Medan Helvet, and Merdeka Square raises questions related to the status of sharia law and the socio-economic effects for the community. This research uses a qualitative approach with a field research method and descriptive analysis. The results show that the practice of money changers is generally carried out with various schemes, including the addition of administrative fees of up to 20%, a reduction in the exchange rate, or online transactions. From the perspective of muamalah fiqh, this kind of transaction has the potential to contain riba fadhl due to the additional measure of similar objects, so it is classified as haram. However, if the contract used is ijarah - with a clear and transparent fee - then the transaction can be justified under Islamic law. On the other hand, this practice provides economic benefits to consumers who need money quickly, although it comes with the risk of spreading counterfeit money, disturbing public order, and unwittingly violating sharia norms. This research contributes to understanding the application of Islamic law to contemporary economic phenomena and recommends the need for stricter regulations from relevant authorities and Islamic law education for the community.